Cash Flow Duration and the Term Structure of Equity Returns - Michael Weber (Center for Economic Studies and ifo Institute (CESifo), 2016)
The term structure of equity returns is downward-sloping: stocks with high cash flow duration earn 1.10% per month lower returns than short-duration stocks in the cross section. I create a measure of cash flow duration at the firm level using balance sheet data to show this novel fact. Factor models can explain only 50% of the return differential, and the difference in returns is three times larger after periods of high investor sentiment. I use institutional ownership as a proxy for short-sale constraints, and find the negative cross-sectional relationship between cash flow duration and returns is only contained within short-sale constrained stocks.
Keywords: E43; G12; G14; 330; dividend strips; short-sale constraints; anomalies; sentiment